Is core stability a risk factor for lower extremity injuries in an athletic population? A systematic review - De Blaiser, C.; Roosen, P.; Willems, T.; Danneels, L.; VandenBossche, L.; De Ridder, R. (Physical Therapy in Sport, 2018)
Objectives: To research and summarize the literature regarding the role of core stability as a risk factor in the development of lower extremity injuries in an athletic population. Methods: Pubmed, Web of Science and Embase were searched in August 2016 to systematically review studies, which related core muscle functioning and core stability to lower extremity injuries. Results: Nine articles were included in the systematic review. Various components of core stability were found to be related to lower extremity musculoskeletal injuries in healthy athletic populations. Core strength, core proprioception and neuromuscular control of the core were found to be a risk factor in the development of lower extremity injuries. However, conflicting evidence was found for core endurance as a risk factor for lower extremity injuries. Conclusion: This systematic review provides preliminary evidence for the association between impaired core stability and the development of lower extremity injuries in healthy athletes. Deficits in various aspects of core stability were identified as potential risk factors for lower extremity injuries. As such, core stability needs to be considered when screening athletes.